Human Factors Evaluation in Ship Design: A Case Study on Offshore Supply Vessels in the Norwegian Sea, Part I: Theoretical Background and Technical Constructs - Rumawas, Vincentius; Asbjørnslett, Bjørn Egil; Kløckner, Christian (Wiley for American Society of Naval Engineers, 2016)
Surveys were conducted in the Norwegian Sea to evaluate the existing human factors standards and their implementations on two different offshore supply vessels designs. The results are reported in two parts. This paper (Part I) covers the theoretical background and reports all the technical aspects of the research: noise, motion and slamming that includes measurements, analyses and evaluations. Noise level and motion were measured by means of sound level meter and accelerometer respectively. Data were collected in two periods: summer and winter. Results of measurements were compared with the existing criteria and discrepancies are identified. It can be concluded that some of the existing human factors criteria are inadequate and less relevant to the actual experience on board and they are ineffective to induce comfort on both supply vessels studied. Improvements and revisions are strongly recommended with respect to noise, motion and slamming criteria. An extended methodology to predict MII is also advised. The other paper (Part II) reports the human factors subjective evaluation performed by the seafarers where multivariate analyses were performed to reveal a human factors model in ship design and operations. submittedVersion This is the pre-peer reviewed version of an article, which has been published in final form at [https://www.ingentaconnect.com/contentone/asne/nej/2016/00000128/00000004/art00019]. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving.